First clinical application of the novel 6.3 Fr disposable digital flexible ureteroscope for treatment of lower calyx renal stones in anticoagulated patient - Xiang Xu; Feihong Xu; Kaifeng Mao; Weiyong Zhong; Mi Zhang; Wenyan Huang; Xiaobao Cheng; Zhenquan Lu; Genggeng Wei (Urology Case Reports)
Managing urinary tract stones in patients on anticoagulant therapy is challenging due to increased bleeding risks. Flexible ureteroscopy (FURS) offers a low-bleeding-risk alternative. A 75-year-old female on Edoxaban for atrial fibrillation presented with recurrent hematuria and a right renal lower calyx stone. FURS using a 6.3 Fr disposable ureteroscope and 10/12 Fr suctioning ureteral access sheath successfully cleared the stone with no complications. The 6.3 Fr disposable digital flexible ureteroscope is effective for managing renal stones in anticoagulant patients, reducing bleeding risks, ureteral injury, and infection. Further research is needed for broader patient applications.